Intellectual Capital and Corporate Sustainable Growth: An Empirical Study on Indian Agribusinesses specific to Pesticides and Fertilizer Companies - Vaishnavi Balaji; Rajesh Mamilla (Qubahan Academic Journal)
This study aims to evaluate the impact of Intellectual Capital on the Sustainable Growth Rate of Indian Agribusiness companies. Intellectual Capital plays a vital role in the global agriculture business. Data is collected from 17 Agribusiness companies engaged explicitly in pesticides and fertilizers between 2011 and 2022, using Prowessiq (CMIE) and financial reports. The Extended Value-Added Intellectual Capital (E-VAIC) model is employed to measure Intellectual Capital. The System Generalized Method of Moments (S-GMM) regression method is employed for data analysis. The results revealed that Innovation Capital Efficiency and Human Capital Efficiency are the most significant variables that affect the Sustainable Growth of Indian Agribusiness companies. The other Intellectual Capital variables, such as Relational Capital Efficiency and Structural Capital Efficiency, positively impact the Sustainable Growth Rate. The study concludes that Indian Agribusiness companies must recognize the importance of Intellectual Capital resources and invest in them to achieve long- term corporate growth.